2007
DOI: 10.1038/sj.ejcn.1602655
|View full text |Cite
|
Sign up to set email alerts
|

Stability of whole blood and plasma ascorbic acid

Abstract: The objective of this study was to evaluate the impact of pre-analytical factors on the short and long term stability of ascorbic acid (AA), the main form of vitamin C in whole blood and plasma. The effects of various anticoagulants, acidification, storage temperature and time were tested. A recently developed fast and sensitive HPLC method was used to measure AA levels. AA baseline values observed in heparin plasma were significantly higher than values observed in EDTA, citrate and Stabilyte plasma, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 19 publications
9
59
1
Order By: Relevance
“…6 As shown by many previous studies, vitamin C maintained at room temperature and exposed to light was dramatically unstable in whole blood. 4,22,23 It is well known that vitamin C in plasma or serum is readily oxidized by oxygen, high temperature, light, pH, ionic strength, solvents, oxidizing enzymes and interaction with iron and copper. 4 Results from our work showed a 22.5% decrease after 6 h in whole blood and more than a 50% decrease after 24 h. Stability of vitamin C depended in part on the type of anticoagulant used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 As shown by many previous studies, vitamin C maintained at room temperature and exposed to light was dramatically unstable in whole blood. 4,22,23 It is well known that vitamin C in plasma or serum is readily oxidized by oxygen, high temperature, light, pH, ionic strength, solvents, oxidizing enzymes and interaction with iron and copper. 4 Results from our work showed a 22.5% decrease after 6 h in whole blood and more than a 50% decrease after 24 h. Stability of vitamin C depended in part on the type of anticoagulant used.…”
Section: Discussionmentioning
confidence: 99%
“…4,22,23 It is well known that vitamin C in plasma or serum is readily oxidized by oxygen, high temperature, light, pH, ionic strength, solvents, oxidizing enzymes and interaction with iron and copper. 4 Results from our work showed a 22.5% decrease after 6 h in whole blood and more than a 50% decrease after 24 h. Stability of vitamin C depended in part on the type of anticoagulant used. As described by Karlsen et al, heparin, EDTA and serum matrix gave the highest baseline concentrations of vitamin C. 4 However, in each matrix, vitamin C concentration decreased rapidly and the more stable matrix seemed to be heparin as the authors reported a loss of less than 5% at 3 h in whole blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Ascorbic acid has also been used as a QC marker for blood pre-centrifugation delay and serum storage conditions owing to its intrinsic instability. 32,33 Pitfalls are readily apparent in even these examples of anlaytes proposed as potential QC tools.…”
Section: Biospecimen Sciencementioning
confidence: 99%
“…However, only a few studies have described the simultaneous determination of AA and UA. Several pre-analytical procedures are required for an accurate and reliable determination of these two antioxidants in human plasma, mainly because AA is extremely sensitive to oxidation and degradation during blood sampling, handling, storage, and analysis [20,21]. Additionally, it is necessary to stabilize the plasma samples by protecting them from light and high temperatures, as well as acidifying the samples before storage, particularly when it is not possible to immediately perform the analysis.…”
Section: Introductionmentioning
confidence: 99%